The Role of Social Media in New Movie Marketing - Griffin, Hali (2012)
The study aims to enhance understanding of social media’s impact on and role within marketing strategy for new release films. Current literature on social media and film marketing has a predominantly consumer-oriented focus. This study examines perceptions of social media from the perspective of marketing practitioners, including knowledgeable filmmakers and other professionals with film marketing expertise. This study utilized semi-structured interviews to explore professional perspectives on: how well social media strategy is being conducted and by whom, how social media campaigns are deemed successful (or unsuccessful), and how essential social media strategy is viewed as a component of the marketing mix for new films.